+0  
 
0
124
1
avatar

how do you use substitution for y=4 3x-y=1

Guest Mar 14, 2017
 #1
avatar+87293 
+5

y=4     3x-y=1        just sub for y in the second equation

 

3x - 4 = 1      add 4 to both sides

 

3x  = 5         divide both sides by 3

 

x =  5/3

 

 

cool cool cool

CPhill  Mar 14, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.